(untitled) (International Journal of Physiotherapy, 2014)
Background: To study the effect of indoor air pollution levels on postural balance control among Saudi school students. Methods: Ninety healthy students (age from 12-16 years) were selected randomly from several preparatory schools representing two areas of different air pollution load and sources in the Eastern Province of Saudi Arabia (group A and B). Levels of carbon monoxide gas (CO), volatile organic compounds (VOCs) and particulate matter less than 10 microns (PM10) were measured at different sites inside the selected schools. The postural control was measured for each participant using Biodex Balance System in bipedal stance with eyes open at the most and least stable levels for 20s. Results: There was no statistical significant difference for the mean values of overall stability index between both groups A and B at the most stable level (p=0.17), while there was a statistical significant difference at the least stable level with mean ± SD of group A and B 2.01±0.48 and 2.61±0.68 respectively. In addition, there were statistical significant differences between the mean levels of all measured air pollutants and overall stability index at the two stability levels in both groups (p<0.01). Conclusion: Indoor air pollution, particularly exposure of students to VOCs, PM10 and CO, has an adverse effect on postural balance control among school students even at low exposure levels.